Свойства и структура алмазных композитов инструментального назначения, полученных из порошков различной дисперсности - Шульженко, А.А.; Соколов, А.Н.; Лошак, М.Г.; Александрова, Л.И.; Заика, Н.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
With use of a method of nanotechniques of magnetic character materials the nanostructural diamond composite material with a medial grit size 0,08 microns and hardness which corresponds to hardness of diamond composite materials with the size of grains 30 microns is gained. Comparative examination of temperature dependence of hardness of diamond nanostructural composites of various dispersibility is carried out. It is displayed, that thermostability of a diamond composite depends not only on a composition of the labilising component, but also from the size of diamond dusts. The gained effects specify in perspectivity of use of the gained material for a finish machining of nonferrous metals and alloys instead of natural diamonds.